2012
DOI: 10.3390/buildings2020063
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Analysis of Historic Masonry Buildings: The Vicarious Palace in Pescia (Italy)

Abstract: Recent Italian earthquakes have underlined the need for wide monitoring and safety assessment of architectonical heritage. This has emerged also from requirements of the new Italian Technical Recommendations for buildings. Within this subject the paper investigates the seismic vulnerability of a specific monumental masonry building: the Vicarious Palace (Palazzo del Vicario) in Pescia, a small town near Florence. The structural behavior of the Palace was investigated using a finite element model in which the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…[8] This paper aimed on the provisions that apart from the recent methods which are well acknowledged in the codes of practice, there are some other old traditional earthquake resistant methods which have verified to be in effect for resisting earthquake loading and are also cost effective with easy constructability and various recommendations for earthquake resistant structures are provided in it also. 9) Michele Betti and Luciano Galano 2012 [9] The paper investigated the seismic susceptibility of a specific monumental masonry structure. The structural behaviour of the Palace was examined using a finite element model in which the non-linearity of the masonry was considered by proper constitutive assumptions.…”
Section: Review Of Literaturementioning
confidence: 99%
“…[8] This paper aimed on the provisions that apart from the recent methods which are well acknowledged in the codes of practice, there are some other old traditional earthquake resistant methods which have verified to be in effect for resisting earthquake loading and are also cost effective with easy constructability and various recommendations for earthquake resistant structures are provided in it also. 9) Michele Betti and Luciano Galano 2012 [9] The paper investigated the seismic susceptibility of a specific monumental masonry structure. The structural behaviour of the Palace was examined using a finite element model in which the non-linearity of the masonry was considered by proper constitutive assumptions.…”
Section: Review Of Literaturementioning
confidence: 99%
“…During the reconstruction of the building in the 1960s, three reinforced concrete rings in the level of the dome's support were constructed to reduce the radial outward forces in the button of the dome, which leads to the significant beneficial effect on the dome's behavior under the gravity load. Funiciello et al (1995) Roman Colosseum Güler and Celep (2003) Hagia Sophia Alper (2004) Hagia Sophia Miltiadou-Fezans 2008Dafini Catholic temple Static, nonlinear Sinopoli and Di Pasquale (2007) Colosseum Anzani et al (2010) (Theoretic approach) Dynamic, nonlinear Betti and Vignoli (2008) Italian Romanesque church Betti and Vignoli (2011) Santa Maria church Betti and Galano (2012) Vicarious palace, Masonry building San Francesco church (Italy) Clementi et al 2016Ferraro et al 2016Historic center(City of L' Aquila) (Italy) Hacıefendioğlu and Koç 2016Historic masonry bridges Clementi et al (2016) Strategic building in catania (Italy)…”
Section: Architecture Of Soltaniyeh Dome and Existing Damagesmentioning
confidence: 99%
“…At the same time, they showed that the use of three-dimensional finite element (FE) models requires a great amount of computational resources, which may be justified only in the case of historical and/or monumental buildings [9][10][11]. Analyzing traditional buildings, the need emerges for simplified, but effective (and reliable) models for the assessment of the global structural response through non-linear time-history analysis methods.…”
Section: Open Accessmentioning
confidence: 99%